2018
DOI: 10.3892/etm.2018.7013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with primary malignant bone and soft tissue tumor aged 65�years or older

Abstract: The number of elderly patients with sarcoma (65 years or older) has increased with the rise in the aging of society. As it is difficult to treat elderly sarcoma patients in the same manner as younger patients, the present study sought to compare treatment options currently available for elderly patients. The present study was comprised 34 Japanese patients (21 men and 13 women) with malignant bone or soft tissue tumors who underwent surgery in our department from September 2004 to March 2014. The median patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
9

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
8
9
Order By: Relevance
“…The predictors of survival time in patients with high-grade STS include tumor size, histology, grading, margin status at resection and the presence of pre-surgical metastasis ( 5 ). It has been previously indicated that old age affects the prognosis of STS ( 15 ), but in the cohort of the present study, with an average age of 66.2 years (range, 39-86 years), the age difference between the two study groups was not statistically significant. The standard treatment of high-grade STS includes surgical resection, with radiation therapy as a supplementary treatment and chemotherapy added if required.…”
Section: Discussioncontrasting
confidence: 88%
“…The predictors of survival time in patients with high-grade STS include tumor size, histology, grading, margin status at resection and the presence of pre-surgical metastasis ( 5 ). It has been previously indicated that old age affects the prognosis of STS ( 15 ), but in the cohort of the present study, with an average age of 66.2 years (range, 39-86 years), the age difference between the two study groups was not statistically significant. The standard treatment of high-grade STS includes surgical resection, with radiation therapy as a supplementary treatment and chemotherapy added if required.…”
Section: Discussioncontrasting
confidence: 88%
“…Our previous study showed that the 5-year survival rate of elderly sarcoma patients was 86% [17]. In the current study, the 3-year survival rate was poorer (61.36%) than those previously reported [17] and that of elderly patients in our hospital. There was also no signi cant difference in survival rates based on age among these AYA patients.…”
Section: Discussioncontrasting
confidence: 72%
“…Our previous study showed that the 5-year survival rate of elderly sarcoma patients was 86% [18]. In the current study, the 3-year survival rate was poorer (61.36%) than those previously reported [18] and that of elderly patients in our hospital. There was also no significant difference in survival rates based on age among these AYA patients.…”
Section: Discussioncontrasting
confidence: 72%
“…The 5-year survival rate in AYA sarcoma patients is approximately 70% [10,17], although prognoses in AYA patients may vary depending on age [17]. Our previous study showed that the 5-year survival rate of elderly sarcoma patients was 86% [18]. In the current study, the 3-year survival rate was poorer (61.36%) than those previously reported [18] and that of elderly patients in our hospital.…”
Section: Discussioncontrasting
confidence: 65%